Effects of patient position on lower extremity venous pressure during different types of hysterectomy. Issue 1 (27th August 2014) - Liu, Xiaoxia; Wang, Xiaohong; Meng, Xianhua; Wang, Hongping; An, Zengshun
Abstract Aim To explore the effects of different types of hysterectomy on lower extremity venous pressure. Methods Ninety‐nine patients with benign uterine diseases who were indicated for hysterectomy were included in the present prospective study. Patients were divided into three groups according to their preferences: (i) total laparoscopic hysterectomy (TLH) group (n = 36); (ii) transvaginal hysterectomy (TVH) group (n = 32); and (iii) transabdominal hysterectomy (TAH) group (n = 31). Lower extremity venous pressure was monitored using a pressure sensor during the surgery. Results Compared with the supine position (TAH group, lower extremity venous pressure of intraoperative 16.50 cmH2O), lower extremity venous pressure of the improved lithotomy position (TLH group, lower extremity venous pressure of intraoperative 53.27 cmH2O) and conventional lithotomy position (TVH group, lower extremity venous pressure of intraoperative 42.09 cmH2O) were significantly increased (P < 0.01).Venous pressure was reduced when patients lowered their heads by 15° or 5° in modified or conventional lithotomy positions, respectively (P < 0.01). Venous pressure was increased significantly after the establishment of pneumoperitoneum in the TLH group (P < 0.01). Conclusion Modified lithotomy position (TLH group) and conventional lithotomy position (TVH group) and CO2 pneumoperitoneum may result in increased lower extremity venous pressure during hysterectomy. Furthermore, elevated venous pressure can be altered by changing the intraoperative position. Specifically, intraoperative positioning of the lower extremities represents a modifiable risk factor for deep venous thrombosis.